Adrenal insufficiency is common amongst kidney transplant recipients receiving maintenance prednisolone and can be predicted using morning cortisol. Issue 1 (13th May 2022) - Tomkins, Maria; Martin-Grace, Julie; Kennedy, Carmel; McEnroe, Olive; Heverin, Karen; Srinivasan, Shari; Little, Dilly; Conlon, Peter; De Freitas, Declan; Denton, Mark; Magee, Colm; O'Seaghdha, Conall; et al.
ABSTRACT: Background: Long-term glucocorticoid therapy is a key component of immunosuppression for kidney transplant recipients (KTRs), leading to significant cumulative glucocorticoid exposure. The aims of this study are to investigate the prevalence of adrenal insufficiency (AI) in KTRs taking prednisolone and to develop a screening algorithm to identify patients at the highest risk of AI. Methods: In this cross-sectional cohort study, 67 KTRs receiving prednisolone underwent a short synacthen test (SST) and measurement of cumulative glucocorticoid exposure. Results: A total of 72% ( n  = 48) of participants failed the SST. Participants with AI had a higher daily prednisolone dose (4.9 versus 4.2 mg/day; P  = .002) and greater cumulative glucocorticoid exposure (289 versus 111 mg/kg; P  = .03) than those with intact adrenal function. Participants with AI had lower baseline cortisol than participants with intact adrenal function (143 versus 303 nmol/L; P  < .001). Morning cortisol of >288 nmol/L predicted a normal SST with 100% specificity [95% confidence interval (CI) 92–100] and 70% sensitivity (95% CI 56–78%), therefore excluding AI. Conclusions: Our results suggest KTRs are at a higher risk for AI than previously reported. A morning serum cortisol measurement is a useful screening tool in this cohort, reducing the need for stimulatory testing by 44%. KTRs with AI need education regarding glucocorticoid sick rules, similar to patients with other forms of AI. Graphical Abstract: